ADAPTATIONS TO AN HIV COUNSELING AND TESTING INTERVENTION FROM A COUNSELOR PERSPECTIVE. Issue 8 (November 2014) - Mckay, Virginia R.; Dolcini, M. Margaret; Conte, Kathleen P.; Catania, Joseph A.
<x xml:space="preserve">Abstract</x> Understanding the balance between fidelity and adaptation for evidence‐based interventions has the potential to improve their translation from research to practice. The Translation into Practice study explores variation in program implementation within organizations utilizing the RESPECT program, an HIV counseling and testing intervention. Counselors (N = 70) were interviewed using a semistructured interview guide to examine both the influential factors on, and the subsequent adaptations to, RESPECT. Almost all counselors reported making adaptations (N = 69). Adaptations were made both to key characteristics (mean [M] = 2.24, standard deviation [SD] = 1.3) and to core components (M = 0.5, SD = 0.8). Counselors identified the environmental context and factors within the counseling context as common influences leading to adaptation. These findings suggest adaptations were a routine part of program usage. To improve implementation of the RESPECT program, further research is needed to assess the degree to which adaptations can be made to better meet the needs of agencies and clients without compromising fidelity.